Evaluation of Efficacy and Safety for Kanglaite Injection in the Control of the Malignant Pleural Effusions via Thoracic Perfusion: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Zhu, Guanghui; Wang, Xinmiao; Li, Jie; Zhang, Ying; Gao, Ruike; Zhang, Xiaoxiao; Xu, Bowen; Hu, Jiaqi; Dai, Minghao; Chen, Jiayang (Frontiers in Pharmacology, 2021)
Background: Kanglaite injection (KLTI) is a traditional Chinese medicine (TCM) preparation with anti-tumor activity, which has been used to treat malignant tumors in China. The purpose of this study was to evaluate the efficacy and safety of intrapleural infusion with KLTI in the treatment of malignant pleural effusion (MPE). Methods: Randomized controlled trials (RCTs) on the efficacy and safety of intrathoracic infusion with KLTI in the treatment of MPE were searched from the PubMed, EMBASE, the Cochrane Library, CNKI, VIP, Wanfang and CBM databases. The primary outcome was objective remission rate (ORR). Secondary outcomes included quality of life (QOL) and incidence of adverse events (AEs). The Stata15.1 software and RevMan5.3 software were used to calculate risk ratios (RR) at 95% confidence intervals (CI) and conduct the meta-analysis. Results: This meta-analysis included 20 RCTs, involving 1291 patients. The ORR of intrapleural infusion with KLTI+ chemotherapy drugs in the treatment of MPE was higher than that of chemotherapy alone [relative risk (RR) 1.23; 95%CI; 1.11-1.36, I2=0%, z= 3.876, P = 0.000]. When KLTI is combined with cisplatin or KLTI 200ml is used in every time, it is more advantageous to improve ORR. Moreover, compared with intrapleural infusion of chemotherapy drugs alone, KLTI combined with chemotherapy drugs significantly improved the QOL of patients with MPE (RR 1.28; 95%CI; 1.70-1.53, I2=0%, z= 2.70, P = 0.007). In addition, the participation of KLTI reduced the gastrointestinal reaction (RR 0.79; 95% CI; 0.66-0.96; I2=0%, z = 2.37, P = 0.018) and renal damage (RR 0.468; 95% CI; 0.23-0.945, I2=0%, z = 2.11, P = 0.035) caused by chemotherapy drugs, but did not increase other adverse reactions (P > 0.05). Conclusions: The efficacy and safety of traditional chemotherapy drugs plus KLTI was superior to traditional chemotherapy drugs alone via intrapleural injection in controlling MPE, which suggested that KLTI can be used to treat MPE. However, a more rigorous RCT should be designed and completed before it is widely recommended.